Insulation co-ordination for gas-insulated transmission lines (GIL). - Volcker, O. (IEEE Transactions on power delivery)
In this paper focus is given to the insulation co-ordination of a closed system with integrated surge arresters. The calculations of transient overvoltages are made with typical applications of the integration of GIL in the 400 kV net of overhead lines. The overvoltages in the system are calculated and discussed for system lengths of 1 km and 10 km. Recommendations for such applications for the insulation levels are given. The GIL design configuration, the lightning overvoltages of overhead lines, and the overvoltages in the GIL are discussed under respect of overvoltage protection measures. Together with the use of surge arresters the insulation levels due to overvoltages are discussed. The insulation co-ordination is a very important measure for system optimization. Calculated values found for the insulation level of the GIL were proven with type tests and long duration test set-ups. Some test results are also explained in this paper